Reactions and Feelings to a Close Relative’s Coming Out in a Heterosexual Relationship - Niedlich, Claudia; Steffens, Melanie C.; Dieckmann, Janine (Frontiers in Psychology, 2022)
Which different feelings and reactions do different family members show if an adult family member who has long been perceived as heterosexual discloses their sexual identity as lesbian, gay, or bisexual? Previous studies have investigated reactions of spouses and sometimes children in the U.S.A. This article describes the findings of qualitative interviews and a German-language quantitative survey (N = 188) in which family members were asked about their emotions, experiences during the coming out process, and their use of support options. The samples were recruited via different LGB+ online forums and organizations in Germany, Austria, and Switzerland (age M = 44.08). The results demonstrate that a coming out after years of a heterosexual biography and family life affects adults’ parents and siblings in addition to spouses and children. Siblings were perceived as a supportive group of family members showing calm and mostly positive reactions. Parents mainly reported surprise but also showed on the one hand interest in supporting their children in the coming out process; on the other hand, we find also evidence for negative reactions including rejecting behavior. Children’s coping and well-being depended on the time that had passed since the coming out and their age at the time of the coming out. Spouses felt shocked, angry, and the ground was pulled from under their feet. Comparing the perspectives of these groups of family members, differences between them, and their specific needs are discussed. Practical implications are derived from the support options mentioned, and range from information from books, the internet to professional advice. Spouses report the need of diverse support options, whereas other family members ask friends and other family members for support. Forums, counseling and the possibility to exchange were perceived as a support but were more accessible for women than for men. They provide the chance for a communicative exchange before the stress becomes too strong.